2000
DOI: 10.1023/a:1003943201178
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In order to understand the effect of changing nutrient conditions on benthic microalgae on hard substrates, insitu experiments with artificial substrates were conducted in Kiel Fjord, Western Baltic Sea. As an extension of previous investigations, we used artificial substrates without silicate and thus were able to supply nutrient media with different Si:N ratios to porous substrates, from where they trickled out continuously. The biofilm developing on these substrates showed a significant increase in biovolum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Thus, even with small diffusion boundary layers (see Section 3.2 above), N, P and Fe limitation of primary productivity is widespread among marine phytoplankton. N limitation has also been shown for benthic marine diatoms in the oligotrophic western Baltic Sea [150]. For freshwater habitats, Maberly et al [151] examined nutrient limitation in an upland lake in the UK, and showed N limitation, P limitation and PN co-limitation to similar extents in phytoplankton and periphyton (microphytobenthos plus multicellular benthic algae and mosses).…”
Section: Availability Of Nitrogen Phosphorus and Ironmentioning
confidence: 97%
“…Thus, even with small diffusion boundary layers (see Section 3.2 above), N, P and Fe limitation of primary productivity is widespread among marine phytoplankton. N limitation has also been shown for benthic marine diatoms in the oligotrophic western Baltic Sea [150]. For freshwater habitats, Maberly et al [151] examined nutrient limitation in an upland lake in the UK, and showed N limitation, P limitation and PN co-limitation to similar extents in phytoplankton and periphyton (microphytobenthos plus multicellular benthic algae and mosses).…”
Section: Availability Of Nitrogen Phosphorus and Ironmentioning
confidence: 97%